KERAGAMAN SERANGGA PENGUNJUNG BUNGA KELAPA SAWIT (Elaeis guineensis Jacq) DI PERKEBUNAN SWASTA SINGINGI HILIR, RIAU - Dwi Afrian; Wiwin Windriyanti; Sri Wiyatiningsih (Plumula : Berkala Ilmiah Agroteknologi, 2020)
Palm oil (Elaeis quineensis Jacq) is one of the mainstay commodity crops of non-oil and gas foreign exchange resources for Indonesia. Palm oil flowers emit volatile compounds that can invite insects. The types of insects that visit oil palm flowers vary, not all visit the flowers are able to act as pollinators. This research aimed to study the diversity of oil palm flower insects so that the information obtained could be useful for subsequent conservation activities. Identification carried out up to morphospecies level. The purposive sampling method used to determine the sample plants used to observed the diversity of visitors. Based on observations of diversity in oil palm flowers obtained 16 morphospecies in order of the number of populations namely E. kamerunicus, Gelechiidae sp. 01, Chelisoches sp. Rhabdoscelus sp, Forficula sp, Velinus nigrigenu, Salticidae sp. 1, Formicinae sp.1, Tirathaba sp, Rhinocoris fuscipes, Thrips hawaiiensis, Formicinae sp.2, Metisa sp, Tetragnathide sp. 1, Thomisidae sp. 1, Euchantecona sp. with a dominance index of 0.89, a diversity index of 0.33 and an evenness index of 0.12, which is relatively low.